The Antibacterial Effectiveness of Red Ginger (Zingiber Officinale Roscoe) Essential Oil in Inhibiting The Growth of Staphylococcus Aureus and Streptococcus Mutans - Lukita, Shavilla; Winda Khosasi; Chandra Susanto; Florenly (Biomedical Journal of Indonesia, 2021)
Red ginger extract has a category strong antibacterial effect on Staphylococcusaureus and Streptococcus mutans. Red ginger essential oil has the potential forstronger inhibition. This study aims to compare the antibacterial effectiveness of redginger essential oil against Staphylococcus aureus and Streptococcus mutans. Thedesign of this study was a laboratory experimental design with a factorial completelyrandomized design. The red ginger used in this study was proven to be a species ofZingiber officinale Roscoe. The production of essential oils in this study uses thesteam distillation method. The content of secondary metabolites in red ginger wastested quantitatively by the GC-MS method. Determination of antibacterial activityusing the disc diffusion method. The data were processed using the SPSS 21.0program. The normality of data distribution was tested with the Shapiro-Wilk test,followed by one-way ANOVA, Levene's test, and the Tukey HSD Post Hoc Test. Theresults of the antibacterial test of red ginger essential oil against Staphylococcusaureus (21.21mm Â± 0.315) and Streptoococcus mutans (23.43mm Â± 0.189) provedthat the inhibition power of the category was very strong at a concentration of 75%.